Understanding the participation of mothers in the care for their children with chronic diseases in an Intensive Care Unit - Ananda Miranda Gonçalves; Camila Cazissi da Silva; Luciana Palácio Fernandes Cabeça; Luciana de Lione Melo (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To understand the perception of mothers of children with chronic diseases hospitalized in intensive care unitsabout their participation in the care of their children Method: Qualitative study based on the premises of the Situated Phenomenon Structure Analysis, with 14 mothers, in Campinas, São Paulo. The discourseswere obtained through open interviews from November 2020 to January 2021, analyzed and discussed according to literature on the topic. Results: Three thematic categories emerged - Sharing the Care with the Health Team; Wanting to be a Part of the Child's Care; Trying to Understand the Organizational Culture. Final considerations: The mothers understand that their participation in their children care depends on the children's state of health. In addition, they highlight the importance of an effective and careful communication. It is up to health institutions to review their organizational culture, implementing the Family Focused Care.